PENJATUHAN PIDANA TAMBAHAN BERUPA PENCABUTAN HAK POLITIK TERHADAP PELAKUTINDAK PIDANA KORUPSI (ANALISIS PUTUSAN MA NOMOR 1261/K/PID.SUS/2015) - Rasina Padeni Nasution; Alvi Syahrin; Mahmud Mulyadi; Faisal Akbar Nasution (Universitas Sumatera Utara, 2019)
ABSTRACT The criminal act of corruption is extra ordinary crimes so extraordinary enforcement (extra ordinary enforcement) and extraordinary measures (extra ordinary actions) are required. The form of countermeasures that is done is to drop the extra criminal to the perpetrator. One of the criminal forms provided is an additional crime in the form of revocation of political rights. The removal of political rights as additional criminal can only be imposed in relation to the political office elected by the election process, and can not be imposed permanently or permanently. There must be a definitive time limit on how long the revocation of political rights may be imposed. Insofar as it is done through due process of law which is in addition to the principal penalty imposed. The method used in this study, is analytical descriptive research directed to find out more deeply and analyze additional criminal penalties in the form of revocation of political rights against perpetrators of corruption through the Supreme Court's decision Number 1261 K / Pid.Sus / 2015. The additional criminal arrangements in the form of revocation of political rights are based on the principle of legality, which reads nullum crimen, nulla poena, sine preavia lege (poenali). This indicates that the imposition of an additional criminal in the form of revocation of political rights against the perpetrators of corruption acts in truth is not contradictory to Human Rights with justifiable reasons for the applicable legislation. The consideration of the Panel of Judges in Supreme Court Decision Number 1261 K / Pid.Sus / 2015 states that the criminal act of corruption perpetrated by the perpetrator is a multi-effect crime and extra ordinary crimes so there is no conflict with human rights values ​​such as freedom, equality, autonomy and security. However, in its verdict the judges merely declare the imposition of an additional penalty in the form of revocation of the right to be elected in public office without giving a certain time limit, while through the decision of the Constitutional Court Number 4/PUUVII /2009 has stipulated that the revocation of political rights is considered constitutional with the restriction of rights only valid for up to five years from the time the convicted person has finished his sentence. Article 38 of the Criminal Code determines the revocation of rights shall come into force on the day the court ruling commences. This leads to overlapping of rules between one criminal law product and another and another subsequent problem, namely criminal disparity. On the basis of any overlap that occurs in any additional penal provisions in the form of deprivation of political rights, it is necessary to synchronize the norms, to end the conflict between the laws therein and to extract the values ​​of Pancasila as the source of the law. Keywords: additional criminal, political rights, corruption